High level of HBV DNA virus in the breast milk seems not to contraindicate breastfeeding - (:unkn) unknown (My University, 2014)
Concerns of possible risk of mother to child HBV transmission through breastfeeding arouse when mothers present high levels of HBV DNA in breast milk. Here we describe the case of an HIV-HBV coinfected mother who presents a highly replicative HBV infection postdelivery and showed high level of HBV DNA in breast milk. Despite cumulative exposure to HBV infectious particles during breastfeeding, the child, who had been correctly vaccinated, was not infected by HBV.
Keywords: African Research